Gambaran Pengetahuan tentang Corpus Alienum Mata pada Pekerja Las : Literature Review - Siswoyo Siswoyo; Kushariyadi Kushariyadi; Atik Komaria (Bima Nursing Journal, 2023)
Welding shop is one of the informal work is risk for accidents and occupational diseases. During the welding process workers can be exposed directly by a foreign body or corpus alienum disease of eye. To describe knowledge about the corpus alienum of the eye in welding workers. Database used Google Scholar and Pubmed, Keywords entered into database, articles filtered according to inclusion criteria. Articles tested with JBI Critical Appraisal Tool, and analyzed if score was >50%. The articles discussing about prevalence, the highest prevalence was found to be 80% of welding workers with an occurrence frequency of more than 10 time. Risk factors for corpus alienum are duration of welding, years of experience, age, type of welding, knowledge and use of PPE. The high prevalence of corpus alienum in welding workers is influenced by risk factors and the use of eye protection.